192 Tacrolimus-induced chronic inflammatory demyelinating polyradiculoneuropa- thy (CIDP): a case series. Issue 9 (12th August 2022) - Evans, Matthew; Dahdaleh, Sam; Karunaratne, Kushan; Pritchard, Jane; Rinaldi, Simon; Viegas, Stuart
Abstract : Introduction: Calcineurin inhibitors are used for immunosuppression after solid organ transplantation, and tacrolimus is the most commonly agent used. It is associated with several adverse effects including oppor- tunistic infection, nephrotoxicity, diabetes and increased cancer risk, but less well known is its association with Chronic Inflammatory Demyelinating Polyradiculoneuropathy (CIDP). Case series: We describe 7 cases of patients developing CIDP following tacrolimus treatment post transplantation. There were 3 cardiac, 3 lung and 2 renal transplants. Time since starting tacrolimus to development of CIDP varied widely from 5 months to 14 years. All cases were clinically consistent with CIDP with demyelinating neuropathy on neurophysiology. Intravenous immunoglobulin (IVIg) was tried in 6/7 cases but only showed clinical effec- tiveness in 2 patients, who required long-term treatment 2-monthly while continuing tacrolimus. In 3 of the IVIg non-responders (and 1 patient not trailed on IVIg), immunosuppression was switched to an alternative agent (sirolimus) with long-term resolution of neuropathy. Some cases were confounded: 1 associated with EBV and another CMV viraemia. Conclusion: Various case reports have demonstrated a possible association between tacrolimus and CIDP, but this is the largest case series to date. IVIg responsiveness alone is generally poor, but resolution is possible when switching to alternative agents.